2017
DOI: 10.1159/000480655
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic and Clinicopathological Significance of IGF-1R in NSCLC: a Meta-Analysis

Abstract: Background/Aims: Accumulating studies have reported that IGF-1R (Insulin-like growth factor-1 receptor) is aberrantly expressed in NSCLC (non-small cell lung cancer), but the role of IGF-1R in NSCLC remains controversial. The present paper assessed the precise role of IGF-1R in NSCLC. Methods: We comprehensively searched PubMed, EMBASE, and Web of Science in March 2017. Combined HRs and ORs were used to evaluate the prognostic and clinicopathological significance of IGF-1R in NSCLC respectively. Results: A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 32 publications
(43 reference statements)
2
21
0
Order By: Relevance
“…2). Because post-transcriptional/translational modifications caused inconsistencies between mRNA and protein levels, further analysis of 18 prognosis-related mRNAs with literature review found that IGF1R, vimentin (VIM encoded), and MRP1 (ABCC1 encoded) were prognosis-related proteins in LSCC [43][44][45]. For MRP1, its high mRNA expression was associated better survival status (Fig.…”
Section: Ubiquitination Affects Lscc Patient's Outcome By Regulating mentioning
confidence: 99%
“…2). Because post-transcriptional/translational modifications caused inconsistencies between mRNA and protein levels, further analysis of 18 prognosis-related mRNAs with literature review found that IGF1R, vimentin (VIM encoded), and MRP1 (ABCC1 encoded) were prognosis-related proteins in LSCC [43][44][45]. For MRP1, its high mRNA expression was associated better survival status (Fig.…”
Section: Ubiquitination Affects Lscc Patient's Outcome By Regulating mentioning
confidence: 99%
“…( Zhu et al, 2017 ) Some studies revealed that high expression of IGF-1R and loss of PTEN were associated with poor prognosis in NSCLC. ( Zhao J. et al, 2017 ; Zhao Y. et al, 2017 ) Although biomarkers and therapeutic targets found in NSCLC have made a great contribution to improving the diagnosis and treatment of NSCLC, due to the biological complexity and poor prognosis of NSCLC, more genetic information remains urgently needed to provide reference for precision medical treatment ( Riess et al, 2018 ; Xu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…36 Moreover, high expression of IGF-1 receptor is also significantly associated with poor prognosis in NSCLC. 37 These results may, to some degree, explain why lung cancer patients with DM have a significantly poorer prognosis than those without. However, in contrast, one study reported that DM could delay NSCLC progression by increasing the level of longlived proteins modified with advanced glycation end product, which could lead to beneficial effects.…”
Section: Discussionmentioning
confidence: 96%
“…Evidence has shown that increased serum hemoglobin A1c, C‐peptide, and IGF‐1 levels are significantly correlated with the development and progression of lung cancer . Moreover, high expression of IGF‐1 receptor is also significantly associated with poor prognosis in NSCLC . These results may, to some degree, explain why lung cancer patients with DM have a significantly poorer prognosis than those without.…”
Section: Discussionmentioning
confidence: 99%